Rural development and food security forum 2019 highlights and takeaways. (Metro Manila, Philippines Asian Development Bank, 2020)
The aim of the forum was to prompt governments in the region to provide the leadership and transformative change needed to generate rural prosperity and effective stewardship of land and water resources. Among the topics discussed were the farm income crisis, food insecurity and malnutrition, and rural distress and prosperity challenges. The publication presents an overview of the forum, including key takeaways.
Keywords: Agricultural resources -- Management; Agriculture -- Economic aspects; Electronic books